Pengaruh Atribut Islami, Kelengkapan Produk, dan Harga terhadap Loyalitas Konsumen pada Toko Basmalah Cabang Plumbon, Pandaan, Pasuruan - Nirza Balqisa Mabruroh; Nur Dinah Fauziah (AL-UJRAH, 2024)
In Indonesia, retail sales growth in 2023 has increased to around 4% or in line with Indonesia's economic growth of around 5.5%, according to the Indonesian Retailers Association (APRINDO). The increase in retail is also accompanied by consumptive behavior, the population continues to grow, and the need for consumers to meet their needs. This study is entitled "The Influence of Islamic Attributes, Product Completeness, and Prices on Consumer Loyalty at Basmalah Stores, Plumbon Pandaan Pasuruan Branch" and aims to prove whether there is an influence of Islamic attributes, product completeness, and prices partially and simultaneously on consumer loyalty at Basmalah Stores. Plumbon Pandaan Pasuruan branch. This study uses a quantitative method with a survey method. With a total of 100 respondents selected using the probability sample technique (probability sample) using the Lemeshow formula from all consumers who shop at Basmalah Stores. The analytical method in this study used multiple linear regression analysis with the help of SPSS 25. The results of this study, the t test shows that the independent variable Islamic attributes and price partially have a positive and significant effect on consumer loyalty, while the product completeness variable has no positive and significant effect on consumer loyalty. In the F test of the independent variable Islamic attributes, product completeness and price simultaneously have a positive and significant effect on consumer loyalty. And based on the value of the coefficient of determination shows that 53.4% ​​of consumer loyalty is influenced by the three factors above, while the remaining 46.6% is influenced by other variables not explained in this study.